Meis1 Regulates Nociceptor Development and Behavioral Response to Tactile Stimuli - Cao, Zheng; Huang, Chengcheng; Lu, Fumin; Jiang, Xuequan; Hu, Yong; Cao, Cheng; Liu, Zijing (Frontiers in Molecular Neuroscience, 2022)
Nociceptors in the dorsal root ganglia (DRG) and trigeminal ganglia (TG) are necessary for transmitting pain and itch signals. However, the molecular mechanism regulating nociceptor development remains largely unknown. This study identifies that the transcription factor Meis1 is generally expressed in two groups of sensory neurons in the developing DRG. During prenatal and neonatal stages, approximately 2/3 of Meis1+ neurons are Runx1+ nociceptors, while 1/3 of Meis1+ neurons are NF200+ myelinated neurons. At postnatal stages, Meis1 expression in nociceptors is gradually reduced. Here, we constructed a Meis1 conditional knockout mouse line to selectively delete Meis1 in Nav1.8 lineage nociceptors. Microarray analyses showed that differentially expressed genes in the Meis1 mutant DRG were enriched in pathways related to sensory perception of pain and nervous system development. In addition, Meis1 regulates the expression of some marker genes of Nppb+ neurons and C-LTMRs. Furthermore, Meis1 mutant mice exhibit behavioral deficits in response to light mechanical pain, static touch and chemical itch. Therefore, this study reveals that Meis1 is required to regulate the development of nociceptors.